Collective resistance and institutional change: Feminist movements and victims' organizations in Mexico’s fight against impunity - Septien Dwi Savandha; Adelia Azzahra; Pegi Sugiartini (Universitas Negeri Yogyakarta, 2026)
Mexico faces a crisis of impunity marked by femicidal violence, disappearances, and institutional flaws. This study examines how feminist and victims' groups resist impunity by analysing their strategies, conditions for change, and justice reforms. Using mixed methods, the research analysed 847 events from 2014-2024 through content analysis, along with 32 interviews and 385 documents. Techniques like regression and network analysis identified patterns and key factors. Movements fight impunity by exposing state failures, creating alternative knowledge, using international frameworks, disrupting normalcy, and raising visibility. Events with legal and direct tactics were 3.17 times more likely to prompt responses (p<0.001), and coalitions increased this to 2.21 (p<0.001). Only 5.5% led to documented action, with responses often punctuated and temporary. Organisational efforts between feminist and victims' groups grew from 12.7% (2014-2019) to 31.4% (2020-2024), showing strategic alignment. Findings reveal an insurgent accountability system where civil society fills state gaps. Effective accountability involves diverse tactics, engaging institutions, external pressure, and strong coalitions. These insights enhance understanding of social movements, accountability, and justice amidst high impunity.